Perception of Patients Regarding Dental Scaling and Aesthetics, Attending Dental Care in a Tertiary Care Hospital - Batool Zara, Fareeha Naz, Sohaib Siddique, Aeman Fatima, Feroze Khan, Beenish Abbas (Pakistan Journal of Medical & Health Sciences, 2022)
Background: There is no as such previous study that takes a glance on the perceptions of general public regarding effects of scaling. The objective of the study was to disregard the misconceptions about post-scaling sensitivity and tooth mobility, to disregard the belief that scaling’s purpose is to whiten the teeth and to figure out how much awareness is there in our society regarding scaling. There is no information regarding the misunderstanding of dental scaling. This study is conducted on general public in Pakistan. Methods: A cross-sectional survey conducted via a close ended questionnaire in the twin cities of Pakistan on a random sample of 238 individuals aged from 18 to 60 years age was conducted in April and May 2020. Results: According to the results,72.3% (172/238) participants were females and 27.7% (66/238) were males. More females had received scaling. 21-22 years age group had the highest scaling experience; also education level was related to scaling. About 87.4% (208/238) of the participants had received scaling once in their life, while 12.6% (30/238) had never experienced scaling. Of the subjects with complete data, 47.9% (114/238) got scaling done for teeth whitening, 39.9% (95/238) were advised scaling by their dentists before any procedure (braces, filing) and 12.2% (29/238) to reduce bleeding gums. Of those who had got scaling done, 44.1% (105/238) participants were scared before getting scaling done, 54.2% (129/238) individuals experienced pain and sensitivity during the procedure, 27.3% (65/238) individuals experienced sensitivity before scaling and 72.7% (173/238) had no sensitivity before the procedure. 56.3% (134/238) experienced sensitivity after getting scaling done, and for most of them this sensitivity was relieved within a week after treatment. 46.6% (111/238) individuals were told by their relatives and friends that scaling would increase their pain and loosen their teeth. 71.4% (170/238) patients were informed by their dentist that sensitivity is a normal part of recovery. 93.3% (222/238) patients found the treatment as beneficial and only 6.7% (16/238) marked it harmful. 92% (219/238) patients said that they would recommend scaling to others due to its beneficial effects. Conclusion: This study shows lack of knowledge regarding scaling among general population. The patients should be properly educated about the procedure and its effects, and clear all the misunderstandings, before the procedure.